Analisis Faktor Yang Memepengaruhi Kesalahan Berbahasa Indonesia Dalam Pembuatan Teks Artikel Ilmiah - Griyani Elisabeth Purba; Nike Margaretha Br Sembiring; Rani Oktavia Purba; Tessa Lonika Simanullang (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Good and correct use of Indonesian is important in communication and writing. However, there are several problems that often arise in the use of Indonesian by students. Errors in the Use of Indonesian in the Mass Media There are errors in the use of Indonesian in the mass media, especially in the school environment. This research uses the type or research approach of Library Research. According to Mestika Zed (2003), library or literature study can be defined as a series of activities relating to methods of collecting library data, reading and taking notes as well as processing research materials. The following are several factors that can influence Indonesian language errors in writing scientific article texts. Not using correct grammar. One of the factors that can cause Indonesian language errors is the inability to use correct grammar. Thus, improving the quality of Indonesian language use needs to be carried out continuously because the changes that occur due to technological advances will influence people's behavior in speaking the language.